ANALYSIS OF COMMUNICATION STRATEGIES IN IMPROVING THE EFFECTIVENESS OF ADMINISTRATIVE TASK IMPLEMENTATION IN THE GENERAL SECTION OF THE NATIONAL UNITY AND POLITICS AGENCY OF LAMPUNG PROVINCE - Zelvia Irvina; Agus Purnomo (International Journal of Multidisciplinary Reseach, 2026)
The research method used is descriptive qualitative research. This method aims to describe the analysis of communication strategies in improving the effectiveness of administrative tasks in the General Section of the National Unity and Politics Agency of Lampung Province. All data were obtained directly from informants in the field using interviews and document studies. The results of the study indicate that, in general, communication strategies in the General Section of the National Unity and Politics Agency of Lampung Province play a significant role in improving the effectiveness of administrative tasks. Communicators have served as a fairly credible source of information, messages are delivered formally, although they still need to be more concise and clear. Communication channels support coordination, but the use of digital media needs to be improved. Furthermore, communicators are generally able to understand and act on information. Overall, strengthening an integrated communication strategy can further improve the effectiveness of administrative performance.